2002
DOI: 10.1034/j.1600-0854.2002.30805.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of a GPI‐Anchored Protein at the Cell Surface Requires Sorting at Multiple Intracellular Levels

Abstract: Proteins modified by glycosylphosphatidylinositol membrane anchors have become popular for investigating the role of membrane lipid microdomains in cellular sorting processes. To this end, trypanosomatids offer the advantage that they express these molecules in high abundance. The parasitic protozoan Trypanosoma brucei is covered by a dense and nearly homogeneous coat composed of a glycosylphosphatidylinositolanchored protein, the variant surface glycoprotein, which is essential for survival of the parasite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 68 publications
(86 reference statements)
3
89
0
Order By: Relevance
“…3C-E [see Fig. 1 and previous studies (Grünfelder et al, 2002;Grünfelder et al, 2003;Overath and Engstler, 2004) for relevant structures and details]. Specific immunolabelling was observed on endosomal cisternae ( Fig.…”
Section: Tbmbap1 Localizes To Endosomesmentioning
confidence: 63%
“…3C-E [see Fig. 1 and previous studies (Grünfelder et al, 2002;Grünfelder et al, 2003;Overath and Engstler, 2004) for relevant structures and details]. Specific immunolabelling was observed on endosomal cisternae ( Fig.…”
Section: Tbmbap1 Localizes To Endosomesmentioning
confidence: 63%
“…In calculation of the relative surface PS density, the mode of PS fluorescence was divided by the average surface area (mm 2 ) of a single African trypanosome or pig erythrocyte (the control) based on published data. 21,22) Incubation of L-and D-type synthetic 9-mer peptides with human brain microvascular endothelial cells (HBMEC). To assess the biocompatibility and/or toxicity of the L-and D-type synthetic 9-mer peptides on host tissues, we used a well-described in vitro model of the human blood-brain barrier (BBB) composed of human brain microvascular endothelial cells (HBMEC).…”
Section: Methodsmentioning
confidence: 99%
“…on VSG trafficking, which have shown that the total VSG complement on the surface of T. brucei is internalized at enormous rate, resulting in a turnover time of 12 min (12,35,43). The fact that it takes more than an hour for the Tf-R to disappear from the surface after the addition of bovine Tf (Fig.…”
Section: Fig 7 Variation Of Tf-r Levels In T Brucei Growing In Culmentioning
confidence: 99%
“…This is unexpected, as trypanosomes are normally able to handle the routing of new VSG efficiently. The Tf-R resembles a VSG dimer in structure and in its glycosylphosphatidylinositol anchor (23), but T. brucei makes at least 100-fold more VSG than Tf-R, and only 11% of this VSG is present intracellularly (12,35,43).…”
Section: Fig 7 Variation Of Tf-r Levels In T Brucei Growing In Culmentioning
confidence: 99%